DEIXIS IN TRANSLANGUAGING PRACTICES: A STUDY ON BILINGUAL CLASSROOM INTERACTION - Angga Maulana; Dian Dia-an Muniroh (STKIP Siliwangi, 2025)
This study intends to identify the types of deixis (personal, temporal, spatial) used in bilingual classrooms, to examine how deixis functions as a linguistic tool to support comprehension in bilingual learning environments, and to provide practical recommendations for lecturers on how to effectively integrate deixis and translanguaging in teaching. To answer the problems, classroom interaction was examined using a qualitative study through classroom observation, audio-recorded interactions, and interviews. The English-speaking Indonesian students and lecturers are participated in this study. According to the results, first, three types of deixis (personal, temporal, and spatial) were identified in bilingual classroom interactions using translanguaging practices. Second, deixis was functioned as an essential language tool for tying communication to particular people, places, and times, which promotes more seamless and contextually relevant interactions. Temporal deixis planned classroom activities, spatial deixis made collaborative work clear, and personal deixis promoted inclusion and relational dynamics. Last, the practical recommendation covered encouraging critical thinking, cultural sensitivity, and participation in multilingual environments. This study emphasizes how crucial it is to incorporate deixis and translanguaging into bilingual education in order to establish welcoming, stimulating, and productive learning environments. To extend these findings across other language and cultural contexts, more study is advised.